Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

What is [(x/2)-(2/x) ]over [(1/2)+(1/x)] simplified?

Pre-cal, I have no clue what i'm doing!!!

5 Answers

Relevance
  • iceman
    Lv 7
    9 years ago
    Favorite Answer

    [(x/2)-(2/x) ] / [(1/2)+(1/x)] => common denominator:

    = [(x^2 - 4)/2x) ] / [(x + 2)/2x)] => factor, simplify

    = [ 2x (x - 2)(x + 2) ] / [2x(x + 2)] => 2x's and (x+2) cancel , you are left with:

    = x - 2

    Edit: added explanation.

  • 9 years ago

    Step 1: You should first simplify the numerator and denominator..

    Therefore: x/2 - 2/x = (x^2 - 4)/2x ---> numerator; where 2x is common denominator.

    1/2 + 1/x = (2 + x)/2x ----> denominator: where 2x is common denominator also.

    Step 2: Rewrite the equation.. it will be....

    [ (x^2 - 4)/2x ] / (2 + x)/2x

    then.. [ (x^2 - 4)/2x ] * 2x/(2 + x) ---- cancel the 2x because 2x/2x = 1

    therefore.. (x^2 - 4) / (2 + x)

    Step 3: Simplify (x^2 - 4)

    ...as you can see.. x^2 - 4 can be rewriten into (x + 2)(x - 2) right? therefore....

    (x + 2)(x - 2) / (2 + x)

    now you cancel the (x + 2).. and the equation will left with (x - 2)..

    Cheeers!!!!! ^_~

  • 9 years ago

    (x/2) - (2/x) = (x^2 - 4)/(2*x) = (x + 2)*(x - 2)/(2*x)

    1/2 + 1/x = (x + 2)/(2*x)

    (x + 2)*(x - 2)/(2*x)/((x + 2)/(2*x)) = x - 2

  • ?
    Lv 5
    9 years ago

    [(x/2)-(2/x)]/ [(1/2)+(1/x)]

    as long as x ≠ 0 or x≠ -2 ; multiply top by x and bottom by x:

    = (x²/2 - 2)/ (x/2 +1)

    multiply top and bottom by 2:

    = (x² - 4)/ (x +2)

    use difference of squares on top:

    = (x - 2)(x +2)/ (x +2)

    cancel out common terms

    = x -2

    remember x ≠ 0, -2 here.

  • 9 years ago

    I am 14 years old...

    [(x/2)-(2/x) ]over [(1/2)+(1/x)] = x-2

Still have questions? Get your answers by asking now.